Molecular Identification of Echinococcus Granulosus(G1) Strain in Human and Animals - Hama, Abdullah A.; Mero, Wijdan M.S.; Jubrael, Jaladet M.S. (Science Journal of University of Zakho, 2013)
Hydatid disease is one of the most common zoonosis with the global distribution caused by the larval stage (metacestode) of small dog tapeworm Echinococcus granulosus that have dual impact on the economic and public health concerns. Ten strain of E. granulosus were identified based on the genetic characterization (G1-G10), the most common strain is sheep strain (G1) which is generally responsible of human Echinococcosis, some other genotypes as G2, G3, G4, G5 and G6 were isolated from human. The molecular identification and strain determination is the initial step for good management and minimizing the infection of CE. This study aimed to identify sheep strain from intermediate hosts including human by polymerase chain reaction (PCR) using specific primer for sheep strain (G1) and detect the genetic variation by sequencing. The specific primer of E. granulosus for sheep strain provide a powerful tool for molecular and epidemiological studies on E. granulosus with possibilities for extension to other genotypes using different molecular targets, the strain identification of E. granulosus is an important point that provide control and management of this disease. The present study showed that the sheep strain is predominant in Kurdistan, all samples were referred to sheep strain and sequence analysis showed slight micro variations within G1.